1. Problem 1 Show that lim x→0 sin(x) =1 x using an − δ proof. Solution: One can see that the following inequalities are true for values close to zero, both positive and negative. | sin(x)| < |x| |x| < | tan(x)| This in turn implies that | cos(x)| < | sin(x) |<1 x On the interval (−π/2, π/2), this implies cos(x) < sin(x) <1 x Subtracting 1 from both sides, we have cos(x) − 1 < sin(x) −1<0 x Taking absolute values, again, we have | sin(x) − 1| < |1 − cos(x)| x This step is important, since we can show that |1 − cos(x)| goes to zero as x does, that is, the right hand side can be found in terms of δ. Since |1 − cos(x)| = | 1 − cos2 (x) sin2 (x) |= ≤ x2 1 + cos(x) 1 + cos(x) Putting this together we have | sin(x) − 1| < x2 x Therefore, if |x − 0| < δ then |f (x) − L| = | Summing up, if |x| ≤ δ = √ sin(x) − 1| ≤ |x|2 ≤ δ 2 x then |f (x) − L| = | sin(x) − 1| ≤ |x|2 ≤ δ 2 = x 2. Problem 2 Using the results of the previous problem, show that lim x→0 sin(sin(x)) x exists. Solution: The easiest way is to write the problem as lim x→0 sin(sin(x)) sin(sin(x)) sin(x) = lim lim x→0 x→0 x sin(x) x Let u = sin(x), then we have lim x→0 sin(sin(x)) sin(u) sin(x) = lim lim = (1)(1) = 1 u→0 x u x→0 x 3. Problem 3 Show that lim sin(1/x) x→0 does not exists, using an − δ proof. Solution: The easiest way is a proof by contradiction. Suppose the limit did exist, then there would be an L such that given an > 0, then |x| < δ would imply | sin(1/x) − L| < . Choose an > 0. Find the δ, depending on . We can find an x-value, e.g. x1 = 1/(N π) such that |x1 | < δ, so that | sin(1/x1 ) − L| = | sin(N π) − L| < |0 − L| < Similarly, we can find an x-value, e.g. x2 = 1/((2N + 1/2)π) so that |x2 | < δ, so that | sin(1/x2 ) − L| = | sin((2N + 1/2)π) − L| = |1 − L| < This is a problem, since if < 1/2, L can’t be close to both 0 and 1! Intuitively, sin(1/x) oscillates to rapidly near x = 0. It takes on values near -1, 0, +1, arbitrarily close to x = 0 so it cannot approach a limit... 4. Problem 4 Show that √ √ lim [ x + 1 − x] = 0 x→∞ Note: To show that lim f (x) = L x→∞ we must show that given any > 0, we can find an N , depending on , such that |x| > N =⇒ |f (x) − L| < The first step is to multiply by the conjugate √ √ √ √ √ √ x+1+ x lim [ x + 1 − x] = lim [ x + 1 − x][ √ √ ] x→∞ x→∞ x+1+ x = lim √ x+1−x √ x+1+ x = lim √ 1 √ x+1+ x x→∞ x→∞ The critical observation is that this can be estimated in terms of N . √ So if |x| > N > 4/2 , then |√ 1 1 1 √ < 2√ < 2√ x x+1+ x N 1 2 2 √ | < |√ | < √ | < x x+1+ x N This gives the relationship between N and explicitly. 5. Problem 5 The Fibonacci numbers are defined by the relationship an+1 ≡ an + an−1 , n = 1...∞ with a0 = 1, a1 = 1. What we want to show is that √ √ √ √ 5+ 5 1+ 5 n 5− 5 1− 5 n ( ) + ( ) a(n) = an = 10 2 10 2 for all integer values of n. This is an indication that we must use induction. First we show that it is true for n = 1. √ √ √ √ √ √ 5+ 5 1+ 5 0 5− 5 1− 5 0 5+ 5 5− 5 a(1) = ( ) + ( ) = + =1 10 2 10 2 10 10 which is true. Now asssume that is true for n ≤ k, that is √ √ √ √ 5+ 5 1+ 5 k 5− 5 1− 5 k ( ) + ( ) a(k) = 10 2 10 2 √ √ √ √ 5 + 5 1 + 5 k−1 5 − 5 1 − 5 k−1 ( ) + ( ) a(k − 1) = 10 2 10 2 Then we examine a(k + 1) = a(k) + a(k − 1) = √ √ √ √ 5+ 5 1+ 5 k 5− 5 1− 5 k ( ) + ( ) 10 2 10 2 √ √ √ √ 5 + 5 1 + 5 k−1 5 − 5 1 − 5 k−1 + ( ) + ( ) 10 2 10 2 and by combining common terms, √ √ √ √ √ √ 5 + 5 1 + 5 k−1 1+ 5 5 − 5 1 − 5 k−1 1− 5 = ( ) (1 + )+ ( ) (1 + ) 10 2 2 10 2 2 The crucial observation is that √ √ √ 1+ 5 2 1+2 5+5 1+ 5 ( ) = =1+( ) 2 4 2 so ( Therefore, √ √ √ 1 + 5 k+1 1 + 5 k−1 1+ 5 k ) =( ) +( ) 2 2 2 √ √ √ √ 5 + 5 1 + 5 k+1 5 − 5 1 − 5 k+1 a(k + 1) = ( ) + ( ) 10 2 10 2 To get the asymptotics, note that an √ √ 5+ 5 1+ 5 n ( 10 2 ) =1+ and since √ √ 5− 5 1− 5 n √ ( √ ) 5+ 5 1+ 5 √ 1− 5 √ |<1 1+ 5 √ 1− 5 n √ | →0 | 1+ 5 | hence √ an √ 5+ 5 1+ 5 n 10 ( 2 ) Therefore c = √ 5+ 5 10 and r = √ 1+ 5 2 . →1 6. Problem 6 Show that one can compute π by means of the infinite series 1 1 1 1 1 + − + − + ...) 3 5 7 9 11 π = 4 ∗ (1 − = ∞ X (−1)n n=0 1 2n + 1 Solution: The function tan−1 (x) can be written as Z Z 1 −1 tan (x) = dx = (1 − x2 + x4 − x6 + ...) 1 + x2 =x− x3 x5 x7 + − + ... 3 5 7 Substituting x = 1, we have π/4 = tan−1 1 = 1 + 1 1 1 1 1 + − + − + ... 3 5 7 9 11 7. Problem 7 Show that the non-alternating series ∞ X 1 2n +1 n=0 diverges. One can do this several ways. The direct approach is to group terms. If we take k successive terms, staring with 2N1+1 we have (taking k of the smallest terms as a lower bound) 1 1 1 1 + + + 2N + 1 2N + 3 2N + 5 2N + 2k − 1 k 2N + 2k − 1 This will be greater than a fixed constant, e.g. 1/4, if ≥ 1 k ≥ 2N + 2k − 1 4 that is, if k ≥ N − 1/2. So, letting k = N we have the inequality 1 1 1 1 + + + = 2N + 1 2N + 3 2N + 5 2N + 2k − 1 1 1 1 1 + + + 2N + 1 2N + 3 2N + 5 2N + 2N − 1 1 N ≥ ≥ 4N − 1 4 Since we have an infinite number of these groups, all of which are greater than 1/4, the series diverges. Another way of demonstrating this is to compare the series to an integral. Using the left hand rule for Riemanns sums Left Hand Endpoint Riemann Sum y 1 f(x)=1/x 1/2 1/3 1/4 1 This implies that 1+ 2 3 4 5 x ∞ ∞ X X 1 1 1 1 1 1 + + ... = ≥ = + + ... 3 5 2n + 1 2n 2 4 n=0 n=1 = 1 1 1 1 1 1 1 [1 + + + ...] ≥ [1 + + + ... + ] 2 2 3 2 2 3 N Z 1 N 1 1 ≥ dx = ln(N ) 2 1 x 2 As N → ∞, the integral (and therefore the sum) become infinite. This is known as an integral comparison test. 8. Problem 8 See the file probem8.pdf 9. Problem 9 Define the Heaviside function by ( 0 H(t) ≡ 1 if t < 0 if t ≥ 0 Show, uising an − δ argument that limit of H(t) as t → 0 does not exist. Solution This is very similar to Problem 3. Again, one uses a proof by contradiction. Suppose the limit did exist, then there would be an L such that given an > 0, then |x| < δ would imply |H(x) − L| < . But, for any δ > 0 we can find two x values such that we must have |H(x1 ) − L| = |0 − L| < and |H(x2 ) − L| = |1 − L| < . This leads to a contradiction if > 1/2. 10. Problem 10 Show that lim xx = 1 x→0+ Solution Since xx = (eln x )x = ex ln x , we can use the properties of the limits, and the fact that ex is continuous, to show that lim+ xx = lim+ ex ln x = elimx→0+ x ln x x→0 x→0 To calculate the last limit, we use L’Hôpital’s rule. lim x ln x = lim x→0+ x→0+ ln x 1/x = lim = lim −x = 0 + 1/x x→0 −1/x2 x→0+ Therefore, lim xx = elimx→0+ x ln x = e0 = 1 x→0+ You can check this out on a calculator for values very close to 0.0